Sufistik Guru Sekumpul - Sahrul Arifin; Abdul Sani; Abdul Hakim; H. Ibnu Arabi (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
M. Zaini Ghani bin Abdul Ghani or known as Guru Sekumpul is a well-known scholar in the South Kalimantan region whose work traces back to the land of Sekumpul, Martapura, South Kalimantan. During his life, he had made extraordinary services for the Muslims there, his extraordinary jihad deserved the greatest appreciation. This is evidenced by the large number of congregations in the submission. Even after he died, the haul congregation continued to grow every year. During his lifetime, Guru Sekumpul forbade the teachings of Sufism, one of which was a way to cleanse the heart. This is where his Sufi values can be seen, which until now has been used as a role model for the wider community, especially the people of Kalimantan. Keywords: Guru Sekumpul, Sufism, Sufism.   Abstrak M. Zaini Ghani bin Abdul Ghani atau dikenal dengan sebutan Guru Sekumpul merupakan ulama masyhur di wilayah kalimantan Selatan yang kiprahnya berjejak di tanah Sekumpul, Martapura, Kalimantan Selatan. Semasa hidupnya, beliau telah menorehkan jasa yang luar biasa bagi umat Islam di sana, jihad beliau yang luar biasa patut dibeikan apresiasi yang sebesar-besarnya. Hal ini dibuktikan dengan banyaknya jemaah dalam pengajuannya. Bahkan setelah beliau wafat sekalipun, jama’ah haul terus bertambah setiap tahunnya. Semasa hidupnya Guru Sekumpul banyak mengajarkan ajaran tasawuf salah satunya adalah cara membersihkan hati, dari sinilah telihat nilai kesufian beliau yang sampai sekarang dijadikan   suri   teladan   bagi   masyarakat   luas,   khusunya masyarakat Kalimantan. Kata Kunci: Guru Sekumpul, Tasawuf, Sufistik.